2013
DOI: 10.1039/c2pp25358e
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted defluorination of fluorinated substrates and pharmaceuticals by a wide bandgap metal oxide in aqueous media

Abstract: Persistent fluorinated substances, such as the fluorine-bearing pharmaceutical drugs Fluoxetine (FLX; Prozac) and Fluvoxamine maleate (FOM) together with several other substrates (fluorobenzoic acid and fluoroaliphatic model compounds), were photochemically defluorinated and degraded under UVC illumination in relatively good yields in the presence of a wide band gap metal oxide (β-Ga2O3) in heterogeneous aqueous media. The formation of fluoride ions increased with increasing illumination time under an inert ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, the dehalogenation is also verified from the first instants of irradiation, presenting a slightly linear variation throughout the study period (Figure 5c). Furthermore, the data is compatible with the literature, 16 which observes a formation of approximately 2.28 mg L -1 of fluoride after 2 h of irradiation of 35 mg L -1 FLX, and the present study verified 2.2 mg L -1 of fluoride formation for experimental conditions (45 mg L -1 FLX, 1 h, without catalyst), evidencing the tendency of dehalogenation.…”
Section: Effect Of the Initial Concentration Of Flxsupporting
confidence: 92%
See 4 more Smart Citations
“…However, the dehalogenation is also verified from the first instants of irradiation, presenting a slightly linear variation throughout the study period (Figure 5c). Furthermore, the data is compatible with the literature, 16 which observes a formation of approximately 2.28 mg L -1 of fluoride after 2 h of irradiation of 35 mg L -1 FLX, and the present study verified 2.2 mg L -1 of fluoride formation for experimental conditions (45 mg L -1 FLX, 1 h, without catalyst), evidencing the tendency of dehalogenation.…”
Section: Effect Of the Initial Concentration Of Flxsupporting
confidence: 92%
“…During the degradation of FLX, the formation of TFMP and the release of fluoride ions show a rupture of the ether bond of the compound and other dehalogenation mechanisms ( Figure 6). The mechanism of degradation by radical attack has been reported in the literature, 16 suggesting that photolysis of water allows the formation of highly reactive hydroxyl radicals. In the present study, the formation of hydroxyl radicals was confirmed for the UV/MW reactor by COU.…”
Section: Effect Of the Application Of Different Reactorsmentioning
confidence: 89%
See 3 more Smart Citations